The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2298/pac2003268z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al(Oh)3 particle size on microstructures and strengths of porous MgAl2O4 ceramics

Abstract: Porous MgAl 2 O 4 ceramics were prepared via in-situ decomposition pore-forming (ISDP) technique using Al(OH) 3 and magnesite as raw materials. The influence of Al(OH) 3 particle size (0-44 µm, 44-88 µm, 88-100 µm, 100-150 µm) on the microstructures and strengths of porous spinel ceramics were investigated by means of X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS). The bimodal distributions were observed among all the pore size distributions of the porous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(51 reference statements)
0
7
1
Order By: Relevance
“…The microporous MgO–Al 2 O 3 ceramics with compressive strengths of 10.0–28.5 MPa and apparent porosities of 28.4%–57.9% as well as median pore sizes of 5.29–7.56 μm were prepared using Al(OH) 3 and calcined magnesite as raw materials via a wet mixing route. Compared with our earlier work, 37,38,42,43 the compressive strengths of the microporous MgO–Al 2 O 3 ceramics in the present study were substantially improved. For example, comparing the sample A71.8 of the present work and the sample made from magnesite and Al(OH) 3 as raw materials, 42 the compressive strength rose from 3.90 42 to 13.21 MPa in this study, but only four percentage points apparent porosity were sacrificed, although the same conditions of sintering temperature and no sintering additives were applied.…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…The microporous MgO–Al 2 O 3 ceramics with compressive strengths of 10.0–28.5 MPa and apparent porosities of 28.4%–57.9% as well as median pore sizes of 5.29–7.56 μm were prepared using Al(OH) 3 and calcined magnesite as raw materials via a wet mixing route. Compared with our earlier work, 37,38,42,43 the compressive strengths of the microporous MgO–Al 2 O 3 ceramics in the present study were substantially improved. For example, comparing the sample A71.8 of the present work and the sample made from magnesite and Al(OH) 3 as raw materials, 42 the compressive strength rose from 3.90 42 to 13.21 MPa in this study, but only four percentage points apparent porosity were sacrificed, although the same conditions of sintering temperature and no sintering additives were applied.…”
Section: Resultscontrasting
confidence: 72%
“…To reduce the sintering temperature, the effects of the Al(OH) 3 particle size and TiO 2 addition on the microstructures and strengths of porous MgO-Al 2 O 3 ceramics at 1600 • C were investigated, respectively. Zhi et al 43 found that the median pore size of porous ceramics decreased from 7.9 to 3.4 μm, whereas the strength increased from 1.4 to 10.8 MPa by reducing the Al(OH) 3 particle size from the range of 100-150 to 0-44 μm. This result was attributed to an increased coordination number 44 between the magnesite and Al(OH) 3 particles, which promotes the formation and growth of sintering necks among particles, which then improves the strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Yan et al put forward the lightweight design of using microporous aggregates to replace dense aggregates for fabricating working layer refractories, which can effectively reduce the thermal conductivity of refractories on the basis of ensuring high-temperature service performance. [17][18][19][20][21][22][23][24] For example, lightweight periclase-spinel castable prepared by Yan et al had a lower bulk density of 10.8% and a lower thermal conductivity of 18.8% (1000 • C) compared with conventional castables. 25 This proved that the lightweight design was an effective strategy to reduce the energy loss due to working lining refractories.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Yan et al. put forward the lightweight design of using microporous aggregates to replace dense aggregates for fabricating working layer refractories, which can effectively reduce the thermal conductivity of refractories on the basis of ensuring high‐temperature service performance 17–24 . For example, lightweight periclase–spinel castable prepared by Yan et al.…”
Section: Introductionmentioning
confidence: 99%